Benzyltoluene/perhydro benzyltoluene – pushing the performance limits of pure hydrocarbon liquid organic hydrogen carrier (LOHC) systems. Issue 6 (23rd February 2022) - Rüde, Timo; Dürr, Stefan; Preuster, Patrick; Wolf, Moritz; Wasserscheid, Peter
Abstract : This study presents benzyltoluene/perhydro benzyltoluene as a very favourable liquid organic hydrogen carrier (LOHC) system for potential industrial applications. Abstract : LOHC technologies enable safe and efficient hydrogen logistics using the existent fuel infrastructure. This study presents benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) as a highly attractive technical LOHC system. Compared with the well-established LOHC systems toluene/methylcyclohexane and dibenzyltoluene (H0-DBT)/perhydro dibenzyltoluene (H18-DBT), the H0-BT/H12-B system combines high volumetric storage density and excellent robustness in hydrogenation/dehydrogenation cycles with low viscosity for easy handling under colder operation conditions. Herein, we report repeated hydrogenation and dehydrogenation cycles in semi-continuous operation at 290 °C with a commercial Pt on alumina catalyst and technical quality LOHC material. Reaction rates for both hydrogen uptake and release are generally found higher compared to those of the DBT-based LOHC system under identical reaction conditions. Side-product formation is very low during cycling the H0-BT/H12-BT system and can be traced back to a very low activity towards deep dehydrogenation forming the cyclisation product methylfluorene in four different regioisomers. Furthermore, we present the experimentally determined hydrogenation/dehydrogenation equilibrium of H0-BT/H12-BT in the temperature range between 220 and 360 °C and for total pressures of 1 and 9 barabs .